PRO POOR TOURISM SEBAGAI ORIENTASI PEMBANGUNAN DALAM UPAYA PENGENTASAN KEMISKINAN DI INDONESIA - Mertha, I Wayan (JURNAL KEPARIWISATAAN, 2010)
Poverty has become a global issue and is multidimensional in nature. Some efforts to reduce poverty have been taken and given priority by many countries. In the tourism sector, Pro-Poor Tourism is an approach in which tourism can contribute to reducing poverty. It is a type of tourism that employs holistic apÂproach, with the main goals to provide economic benefits, open job opportuniÂties, and promote decision making to the poor. The approach to reducing poverty through tourism is by direct involvement of the poor in business ownership, providing human resources, providing products and services to tourists.